Facile preparation and characterisation of oxygen-rich reduced graphene oxide for improved electrochemical performance: a preliminary study - Ali Rahman, Mohamad Aliff; Soon, Poh Lee; Kwok, Feng Chong; Yi, Ellie Lih Teo (Institut Kimia Malaysia, 2023)
Graphene is an excellent candidate as an electrode material for supercapacitors due to its exceptional properties. Among the many synthesis routes, reduced graphene oxide (rGO) synthesised through modified Hummers’ method followed by reduction has been the preferred route to obtain graphene due to its flexibility. Depending on the reaction condition, the degree of oxidation present on rGO will differ and affect its overall charge storage capability. But, the use of toxic reagents or harsh conditions will introduce environmental concerns. Herein, an environmental-friendly KCl was introduced to modify the degree of oxidation on rGO using a simple aggregation method. In this study, graphite oxide obtained through modified Hummers’ method was modified with KCl followed by reduction using ammonia to produce chemically-modified rGO (S-rGO).S-rGO obtained was then characterised using UV-Vis and FT-IR while its electrochemical behaviour was studied with cyclic voltammetry. The UV-Vis and FT-IR analyses showed that the oxidation level of S-rGO increased linearly with the mass of KCl used. Specific capacitance calculated from the CV curves revealed that a 3.5 times enhancement was observed. The results revealed the possible modification on S-rGO using environmental-friendly KCl and its potential use as an electrode material for supercapacitors application.